Long-term effects of neoadjuvant chemoradiotherapy followed by sphincter-preserving resection on anal sphincter function in relation to quality of life among locally advanced rectal cancer patients: a cross-sectional analysis - Ozgen, Zerrin (Radiat Oncol, 2015)
BACKGROUND: There is growing recognition for the consequences of rectal cancer treatment to maintain an adequate functional sphincter in the long-term rather than preserving the anal sphincter itself. This study aims to evaluate long-term effects of neoadjuvant chemoradiotherapy (nCRT) followed by sphincter-preserving resection on anal sphincter function in relation to quality of life (QoL) among locally advanced rectal cancer patients. METHODS: Twenty-nine patients treated with nCRT followed by low anterior resection surgery were included in this study. Data on patient demographics, tumor location and symptoms of urgency and fecal soiling were recorded and evaluated with respect to Wexner Fecal Incontinence Scoring Scale, European Organization for Research and Cancer (EORTC) cancer-specific (EORTC QLQ-C30) and colorectal cancer-specific (EORTC QLQ-CR38) questionnaires and anorectal manometrical findings. Correlation of manometrical findings with Wexner Scale, EORTC QLQ-CR38 scores and EORTC QLQ-C30 scores was also evaluated. RESULTS: Median follow-up was 45.6 months (ranged 7.5–98 months. Higher scores for incontinence for gas (p = 0.001), liquid (p = 0.048) and solid (p = 0.019) stool, need to wear pad (p = 0.001) and alteration in life style (p = 0.004) in Wexner scale, while lower scores for future perspective (p = 0.010) and higher scores for defecation problems (p = 0.001) in EORTC QLQ-CR38 were noted in patients with than without urgency. Manometrical findings of resting pressure (mmHg) was positively correlated with body image (r = 0.435, p = 0.030) and sexual functioning (r = 0.479, p = 0.011) items of functional scale, while rectal sensory threshold (RST) volume (mL) was positively correlated with defecation problems (r = 0.424, p = 0.031) items of symptom scale in EORTC QLQ-CR38 and negatively correlated with social function domain (r = −0.479, p = 0.024) in EORTC QLQ-C30. RST volume was also positively correlated with Wexner scores including incontinence for liquid stool (r = 0.459, p = 0.024), need to wear pad (r = 0.466, p = 0.022) and alteration in lifestyle (r = 0.425, p = 0.038). CONCLUSION: The high risk of developing functional anal impairment as well as the systematic registration of not only oncological but also functional and QoL related outcomes seem important in rectal cancer patients in the long-term disease follow-up.